Der Einsatz von Lichtfallen bei der Schädlingsbekämpfung in der römischen Kaiserzeit, 1. Jahrhundert v. Chr. - 4. Jahrhundert n. Chr. (Insecta, Lepidoptera, Pyralidae). - Steiner, Axel (Contributions to Entomology = Beiträge zur Entomologie, 1991)
The use of light-traps in pest control in the Roman Empire, 1st centure B.C. to 4th century A.D. (Insecta, Lepidoptera, Pyralidae). - Roman beekeepers used light-traps for wax moth control as ducumented by Roman agricultural literature (Columella, Plinius, Palladius). These sources are discussed and the light-trap design is described.